Logistics real estate markets: indicators of structural change, linking land use and freight transport - Markus Hesse (European Regional Science Association (ERSA), 2002)
The system of physical distribution that comprises transport and logistics, warehousing and wholesale, is an ideal indicator of structural change. Distribution and logistics have developed dynamically, with respect to new technologies, corporate restructuring, and a changing market environment. Whereas traditional logistics were characterized primarily by the demand of manufacturing customers for the shipment of bulk-commodities, modern production and service systems require frequent deliveries over great distances, with high inventory turnovers instead of storage. As a consequence, the locational profiles of distribution firms have changed as well, both at a large-scale level and within metropolitan regions. Based on recent findings of the European Warehousing Index, the paper points out how the European system of goods movement has changed in terms of regional distribution markets and warehousing location. Secondly, the consequences of locational dynamics within metropolitan regions are considered. The dominance of the truck and the suburbanisation of large distribution centres raise serious concern about logistics management, traffic reduction and locational policy. Referring to selected places such as the Ruhr Area, Hamburg or Berlin-Brandenburg, the paper demonstrates how critical the relationship between cities and goods distribution is becoming, with regard both to the regional economy and the urban environment. Is there a chance for regional, spatially oriented management of supply chains? In the case of the Ruhr Area, it is also questioned whether a certain 'knowledge milieu' (logistics research, applied sciences) may contribute to this goal. The particular benefits of investigating logistics real estate markets are fourfold: - They allow for a precise insight into regionally differentiated developments. - They connect the system of 'flows' with material 'space'. - They demonstrate that structural change is by no means neutral for the environment, regarding specific transport and land use implications of distribution. - They represent the emergence of new players in land use planning and policy (i.e. developers), thus shaping the system of political regulation.
Keywords: 330